Systematical Analysis of the Cancer Genome Atlas Database Reveals EMCN/MUC15 Combination as a Prognostic Signature for Gastric Cancer - Dai, Wentao; Liu, Jixiang; Liu, Bingya; Li, Quanxue; Sang, Qingqing; Li, Yuan-Yuan (Frontiers in Molecular Biosciences, 2020)
Digestive cancers, including gastric cancer, colorectal cancer, hepatocellular carcinoma, esophageal cancer and pancreatic cancer, account for 26% of cancer cases and 35% cancer deaths worldwide in 2018. It is crucial and urgent to develop biomarkers for diagnosis, prognosis and therapeutic benefits for digestive cancers, especially for gastric cancer (GC), since the incidence of GC is only lower than lung cancer in China, and it is hard to be detected at early-stage and associated with poor prognosis. Mucins, glycoproteins encoded by MUC family genes, act as part of physical barrier in digestive tract and participate in various signaling pathways. Some mucins have been used or proposed as biomarkers for carcinomas, such as MUC16 (CA125) and MUC4. However, there are no systematic investigations on the association of MUC family members with diagnoses and clinical outcomes even though relevant data have been largely accumulated in the past decade. By analyzing transcriptomic and clinical data of digestive cancer samples from TCGA involving colon adenocarcinoma (COAD), esophageal carcinoma (ESCA), liver hepatocellular carcinoma (LIHC), stomach adenocarcinoma (STAD) and pancreatic adenocarcinoma (PAAD), it was found that expressions levels of MUC15, MUC13 and MUC21 were individually associated with survival for digestive cancers, and high expressions of EMCN (MUC14) and MUC15 were correlated with poor survival for STAD. Cox regression analysis indicated predictive power of EMCN/MUC15 combination for overall survival of gastric cancer patients, which was validated on an independent dataset from GEO. EMCN/MUC15 correlated genes were identified to be enriched in cancer related processes, such as vasculature development, mitosis and immunity. Therefore, we propose that EMCN/MUC15 combination could be a potential prognostic signature for gastric cancer.